2006
DOI: 10.1111/j.1440-1746.2006.04361.x
|View full text |Cite
|
Sign up to set email alerts
|

Antifibrotic effects of tetrandrine on hepatic stellate cells and rats with liver fibrosis

Abstract: Tetrandrine exerts antifibrotic effects in both HSC-T6 cells and in rats with DMN-induced fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
80
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 67 publications
0
80
0
Order By: Relevance
“…Silymarin also inhibited TNF-α induced activation of MAPK and JNK, TNF-induced cytotoxicity and caspase activation. Silymarin in combination with tetrandrine attenuates NF-κB activated pathways and the induction of metallothionein gene transcription in the liver of dimethylnitrosamine (DMN) administered rats [20]. In human mesangial cells, silymarin showed dose dependent inhibition of TNF-α-and IL-1β-induced NF-κB activation, and TNF-α-induced intracellular calcium and MCP-1 expression [21].…”
Section: Anti-inflammatory Effects Of Silymarinmentioning
confidence: 99%
“…Silymarin also inhibited TNF-α induced activation of MAPK and JNK, TNF-induced cytotoxicity and caspase activation. Silymarin in combination with tetrandrine attenuates NF-κB activated pathways and the induction of metallothionein gene transcription in the liver of dimethylnitrosamine (DMN) administered rats [20]. In human mesangial cells, silymarin showed dose dependent inhibition of TNF-α-and IL-1β-induced NF-κB activation, and TNF-α-induced intracellular calcium and MCP-1 expression [21].…”
Section: Anti-inflammatory Effects Of Silymarinmentioning
confidence: 99%
“…The pictures of FITC images and those of rhodamine images were merged using Leica image analysis software. Double staining techniques of α-SMA and NFκB p65 were adapted from the report of Kitamura and Ninomiya (2003) and have been established in our laboratory (Chong et al, 2006;Hsu et al, 2007). The method for counting the numbers of α-smooth muscle actin (α-SMA) and NFκB-positive staining was adapted from Parsons et al (2004).…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative PCR analysis was performed using an ABI prism 7900 HT Sequence Detection System (Applied Biosystems, Foster City, CA, USA). In the study, two different methods of quantitative PCR were used (Chong et al, 2006;Hsu et al, 2007): (I) SyBR Green method for the expression of G3PDH, ICAM-1, TGF-β1 and α-SMA genes. SyBR Green, a double-stranded DNA binding dye, was used for the fluorescent detection of DNA generated during the PCR.…”
Section: Introductionmentioning
confidence: 99%
“…Tetrandrine significantly reduced Iκα expression and TNF-α induced NF-κB activity, Iκα phosphorylation and NF-κB nuclear translocation in HSC-T6 cells, reduced the NF-κB activity stimulated by tumor necrosis factor-α (TNF-α) and hydrogen peroxide in HSC-T6 cells, and also reduced the mRNA expression of the NF-κB responsive gene, intra cellular adhesion molecule-1, induced by TNF-α, tetrandrine concentration dependently attenuated TGF-β1 stimulated α-SMA secretion and collagen deposition in HSC-T6 cells [43] . Along this line Lee et al reported tetrandrine treatment prevented liver fibrosis in bile duct ligated rats by suppressing the expression of TIMP-I mRNA of HSCs in fibrogenesis, resulting in reduced expression of collagen lead to promotion of matrix degradation [44] .…”
Section: Tetrandrinementioning
confidence: 99%